Addressing procedural bias in municipal planning governance: A case for incorporating citizen participation within technical advisory committees. Issue 1 (1st March 2015) - Kleinschmit, Stephen
Abstract : This essay presents models of multiparty negotiation as a means to compare the conventional public meetings format of planning to a preliminary process, the technical advisory committee. A metric of market concentration, the Herfindahl-Hirschman Index, is used to quantify the structural advantages in each, and presented within the context of municipal planning processes. In doing so, this work advances several propositions: First, open meetings expand power differentials between parties, which lead to outcomes that reflect the political efficacy of participants over the regulatory purpose of government. Second, such meetings create substantial transaction costs for the public, creating a barrier to the expression of community values. Finally, preliminary processes constitute a more effective forum for citizen participation than open meetings.